Depression and anxiety in patients with breast cancer receiving radiotherapy: a longitudinal study - Shi-Jia Wang; Xin Feng; Wei Zhang; Guang-Yi Sun; Hui Fang; Hao Jing; Yu Tang; Tao Li; Shu-Nan Qi; Yong-Wen Song; Wen-Wen Zhang; Ning-Ning Lu; et al. (Therapeutic Advances in Medical Oncology)
Background: Depression and anxiety are common among patients with breast cancer, but prospective studies of depression and anxiety after radiotherapy (RT) among these patients remain scarce. Objective: To evaluate the prevalence of and changes in depression and anxiety among patients with breast cancer from the first day of RT (T0) to 6 months post-RT, and to identify risk factors associated with depression and anxiety and higher levels of them over time. Design: This observational study used a prospective, longitudinal design. Methods: This study was conducted in China between August 2022 and August 2023. Depression and anxiety were measured, respectively, by Patient Health Questionnaire and the Generalized Anxiety Disorder Scale, from T0 to 6 months post-RT. Univariate and multivariate logistic regressions were performed to explore risk factors for baseline depression and anxiety. Generalized Estimating Equations were performed to evaluate changes in depression and anxiety and risk factors for higher levels of them over time. Results: A total of 504 patients completed baseline questionnaires (response rate: 90.9%). The prevalence of depression and anxiety decreased significantly over time, from 37.3% and 26.0% at T0, to 28.4% and 20.3% at 6 months post-RT, respectively. Having a family history of cancer and receiving anti-HER2-targeted therapy were independently associated with depression at T0, and premenopausal status, poor family income, and self-reported menopausal symptoms were independently associated with both depression and anxiety at T0. Receiving anti-HER2-targeted therapy, having a lower personal income, and living in rural areas were associated with higher depression levels over time, whereas poor family income and self-reported menopausal symptoms were associated with higher anxiety levels over time. Conclusion: Depression and anxiety levels were high among patients with breast cancer receiving RT and decreased over time from pre-RT to 6 months post-RT. Routine screening is necessary, especially for high-risk patients.